Effect of modular neck variation on bone and cement mantle mechanics around a total hip arthroplasty stem. - Simpson, D; Little, J; Gray, H; Murray, D; Gill, H (2009)
BACKGROUND: Total hip arthroplasty carried out using cemented modular-neck implants provides the surgeon with greater intra-operative flexibility and allows more controlled stem positioning. METHODS: In this study, finite element models of a whole femur implanted with either the Exeter or with anew cemented modular-neck total hip arthroplasty (separate, neck and stem components) were developed.The changes in bone and cement mantle stress/strain were assessed for varying amounts of neck offset and version angle for the modular-neck device for two simulated physiological load cases: walking and stair climbing. Since the Exeter is the gold standard for polished cemented total hip arthroplasty stem design, bone and cement mantle stresses/strains in the modular-neck finite element models were compared with finite element results for the Exeter. FINDINGS: For the two physiological load cases, stresses and strains in the bone and cement mantle were similar for all modular-neck geometries. These results were comparable to the bone and cement mechanics surrounding the Exeter. These findings suggest that the Exeter and the modular neck device distribute stress to the surrounding bone and cement in a similar manner. INTERPRETATION: It is anticipated that the modular-neck device will have a similar short-term clinical performance to that of the Exeter, with the additional advantages of increased modularity.